Systematic Review of the Impact of Artificial Intelligence in Higher Education - Figueroa de la Fuente, Mariana; Farhadian, Gelareh (Journal of Teaching and Learning)

(untitled) (University of Windsor, 2025)
Generative AI has undergone a radical transformation, becoming a revolutionary change as important as when the internet appeared. This systematic review explores the impact of AI in higher education, using the principles of Education 4.0 to guide the analysis as a framework. This research used the “Preferred Reporting Items for Systematic Reviews and Meta-Analyses” (PRISMA), based on a review of 243 articles published between 2017 and 2025, to address three main objectives: to systematically examine the existing literature, to explore the opportunities and challenges of AI integration, and to identify gaps for future research. Co-occurrence analysis and data-driven methods, including LDA, BERTTopic, and K-Means clustering, reveal that the interest of the scientific community has been growing, focusing on ethical governance, the enhancement of personalized learning, and the development of faculty AI competencies. These priorities are in line with more general worries about guaranteeing equity, openness, and inclusivity in the use of AI. The statistical analyses and administrative applications, on the other hand, have received less attention and are still ripe for investigation. The comprehension of AI's disruptive role in education is strengthened by this exploratory review, which also suggests ways to advance research and practice in higher education settings.